(3CSGSjGJ GdCOGA h HWGbI GdJbjje GdeJhGRf (B/s - (3GOQjS, hGFd eMeO UHMjs; (3GdZGdHj, WGgQ eMSf efUhQ s ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
1) (3JTNjU GdCOGA (B: (3GdJWhQ GdJGQjNj ddCOGA , ebOeI aj bHGS h EOGQI GdGOGA aj YUQ GdeYdheGJ (B2)(3HWdbjI GdJbjje GdeJhGRf (B: (3eGgjI HWGbI GdJbjje GdeJhGRf , GdefXhQ GdeGdj aj HWGbI GdJbjje GdeJhGRf , efXhQ GdYedGA h GdYedjGJ GdOGNdjI aj HWGbI GdJbjje GdeJhGRf , efXhQ GdJYde h Gdfeh aj HWGbI GdJbjje GdeJhGRf(B.s
(3eQGLY U(B.253 (3; GTcGd (B: (3dcd Tcd UaMI ; LOhd (B: (3dcd LOhd UaMIs
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQIs; (3Jbjje GdCOGAs